2021
DOI: 10.1186/s12961-021-00711-3
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the nature and quality of locally commissioned evaluations of the NHS Vanguard programme: an evidence synthesis

Abstract: Background With innovation in service delivery increasingly viewed as crucial to the long-term sustainability of health systems, NHS England launched an ambitious new model of care (Vanguard) programme in 2015. Supported by a £350 million transformation fund, 50 Vanguard sites were to act as pilots for innovation in service delivery, to move quickly to change the way that services were delivered, breaking down barriers between sectors and improving the coordination and delivery of care. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(48 citation statements)
references
References 18 publications
0
48
0
Order By: Relevance
“…Moreover, implemented initiatives were heterogeneous across sites and difficult to describe in detail using interviews and documentary analysis [15,19,[32][33][34][35][36][37]. A recent evidence synthesis of 115 local Vanguard evaluation reports concluded that none of the reports offered "explanations and/or nuanced insights into the Vanguard operation" [38], making crossinitiatives comparisons difficult. Second, our method does not rule out the possibility that confounding events, unrelated to the integration processes, may have differentially affected the different groups of CCGs being compared in the post-implementation period.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, implemented initiatives were heterogeneous across sites and difficult to describe in detail using interviews and documentary analysis [15,19,[32][33][34][35][36][37]. A recent evidence synthesis of 115 local Vanguard evaluation reports concluded that none of the reports offered "explanations and/or nuanced insights into the Vanguard operation" [38], making crossinitiatives comparisons difficult. Second, our method does not rule out the possibility that confounding events, unrelated to the integration processes, may have differentially affected the different groups of CCGs being compared in the post-implementation period.…”
Section: Discussionmentioning
confidence: 99%
“…Hitherto, the Pioneer or Vanguard programmes have been studied separately [15,19,[32][33][34][35][36][37][38], but never in combination. However, a number of Pioneers subsequently applied to become Vanguards, and thus the two programmes overlapped in time and partially in place.…”
Section: Comparing the Impact Of The Pioneer And Vanguard Programmesmentioning
confidence: 99%
“…Substantial funding was an important influence on the implementation of the Vanguard pilots. 25 However, although funding was effectively ring-fenced around Vanguards, no This meant that many Vanguard initiatives were terminated 19 impacting future initiatives as highlighted by this service commissioner:…”
Section: Dedicated and Ongoing Resourcesmentioning
confidence: 99%
“…Although the local U n d e r R e v i e w 17 evaluation teams fed back interim findings, this was often either too late for Vanguards to change course or there was a desire, and associated pressure, to demonstrate success against nationally determined parameters. 25 This was reflected in tension between some of the Vanguards and their evaluators, where the Vanguards saw the evaluators' role as confirming success rather than using the feedback as a mechanism to learn and refine their activities, as this local evaluator said: 'They thought they were paying us to give us positive results but in order to maintain our integrity we had to be as neutral as possible.' (P1R11) Increasingly, the Vanguards came under pressure to demonstrate success against nationally determined outcome measures that did not necessarily align with local objectives.…”
Section: Ongoing Monitoring and Feedbackmentioning
confidence: 99%
“…20 However, data and findings are limited across the vanguard sites, with questions about the reliability of outcomes data and, consequently, uncertainty about the impact of PACS on key dimensions of health service delivery. 24,25 Five years on from the NHS Five Year Forward View, 21 the 2019 NHS Long Term Plan 26 announced the intention that all general practices in England should combine into PCNs covering populations of 30,000-50,000. 26 Since July 2019, all but a small number of practices have become horizontally integrated in that way with other practices, although remaining separate legal entities with separate contracts.…”
Section: Policy-drivers For Integrationmentioning
confidence: 99%